Psikoedukasi Self-Love pada Remaja Desa Jombok untuk Membentuk Diri yang Positif - Shofwatal Qolbiyyah; Reza Rahmah; Nafi’ Mardliyyatus Sholikhah; Ika Putri Ludviyah; Ratih Maulida Sari D; Vina Novela Sari; Tommy Ari W; Lucky Wahyu Widianto; Mokhamad Romeli (CV. ITTC INDONESIA, 2024)
This study aims to evaluate the effectiveness of a psychoeducation program on Self-Love among adolescents aged 12-18 years in Jombok Village, Ngoro District, Jombang Regency. The activity was conducted on August 9, 2024, involving 23 adolescents as participants. The study used a descriptive quantitative method, with data collected through pre-tests and post-tests to measure participants' understanding of Self-Love. The results showed a significant improvement in participants' understanding, with an average pre-test score of 42.73 and an average post-test score of 84.55. These findings confirm that the delivered psychoeducation materials effectively increased participants' knowledge and awareness of Self-Love, and highlight the importance of similar programs in preventing mental health issues among adolescents.